Structural organization of periodontium and morphological changes in its components in modeled periodontitis and its correction in rats - H. Biguliak; I. Klishch (Kazimierz Wielki University, 2021)
Introduction. The aim of our research was to study peculiar features of morphological changes in the components of the periodontium in the modeled acute periodontitis and its correction by stem cells. Materials and Methods. The results of histological study of periodontal tissues of the animals with acute experimental periodontitis, which was corrected using human mesenchymal stem cells as well as rat muscle stem cells, were analysed. Depending on the treatment, the animals were divided into 4 groups: the 1st group - the animals without pathology (intact); the 2nd - the animals with modeled acute periodontitis; the 3rd - the animals with periodontitis corrected by human mesenchymal stem cells, the 4th - the animals with periodontitis corrected using rat muscle stem cells. Results and Discussion. According to the results of the research it was established that correction by human mesenchymal stem cells and rats muscular stem cells had positive effect on a course of the modeled pathological process. The morphological changes characteristic of periodontitis gradually reduced, i.e. the normal blood supply to the tissues restored, the arteries were less full-blooded, the tone of their walls decreased. Consequently, the swelling of the tissues gradually decreased becoming of original size. The polymorphonuclear infiltration fields decreased and gradually disappeared. Osteoblasts promoted restoration of the bone structure of the jaw alveolar process. The size of the periodontal pocket decreased, and in some areas it fully closed as a result of complete adhesion of the mucous membrane of the gums to the tooth, which rose on its surface upwards. Conclusions. In the experimental modeling of acute periodontitis the destructive changes in the epithelium and connective tissue stroma, impaired blood flow, inflammatory response in the gum tissue were present. The correction by means of human mesenchymal stem cells as well as rat muscle stem cells had positive effect on the modeled pathological process: the morphological changes characteristic of periodontitis gradually reduced, normal blood supply to tissues restored, polymorphonuclear infiltration fields gradually decreased and disappeared. The bone structure of the jaw alveolar process restored owing to osteoblasts. The size of the periodontal pocket decreased; in some cases, they closed completely as a result of complete adhesion of the mucous membrane of the gums to the tooth, which rose on its surface upwards.